Metabolomics integrated with transcriptomics and proteomics: Evaluation of systems reaction to nitrogen deficiency stress in microalgae. (April 2020) - Nagappan, Senthil; Devendran, Saravanan; Tsai, Pei-Chien; Jayaraman, Hariharan; Alagarsamy, Vardhini; Pugazhendhi, Arivalagan; Ponnusamy, Vinoth Kumar
Graphical abstract: Highlights: Review reports on physiological and biochemical reaction to N-stress in microalgae. Lipid and carbohydrate increased and protein decreased in N-stressed cells. During nitrogen deprivation, radicals are overproduced creating oxidative stress. The increase in cellular oxidative stress causes the accumulation of lipids. Abstract: Microalgae have higher productivity of biomass than the conventional crops of fuel and are therefore, considered a potential biofuel source. Lipid, an important precursor of biodiesel, can be overproduced in microalgae by nitrogen deprivation. During nitrogen deficiency, radicals are overproduced, and the antioxidant levels are insufficient to counteract the radicals. Thus, the increase in cellular oxidative stress level, consequently acts as a stimulus for lipid accumulation. Lipid accumulation requires an excess of acetyl CoA and NADPH that is made possible by the following mechanism. Glycolysis upregulation overproduces pyruvate, which could be further transformed into acetyl CoA by the pyruvate dehydrogenase complex; while the upregulation of the oxidative pentose phosphate cycle generates a high amount of NADPH. In addition to lipid overproduction, the lack of nitrogen often causes the accumulation of carbohydrates in selected species of microalgae, which could be used to generate biogas and bioethanol from the defatted biomass. By providing details on the differential regulation of the biochemical pathways leading to lipid and carbohydrate accumulation in nitrogen starved microalgae, the review opens up new possibilities in the microalgal biofuel production.